2004
DOI: 10.1046/j.1365-2761.2003.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of anti‐Neoparamoeba sp. antibodies in Tasmanian cultured Atlantic salmon, Salmo salar L.

Abstract: Previous studies have indicated that when Atlantic salmon, Salmo salar L., are exposed to Neoparamoeba sp. the fish produce anti-Neoparamoeba sp. antibodies. It appears unlikely that these antibodies elicit any specific protection against amoebic gill disease (AGD) as fish with demonstrable activities have been affected by AGD. Experiments were conducted on Atlantic salmon cultured throughout Tasmania to assess the natural production of antibodies towards Neoparamoeba sp. Fish were sampled from areas where AGD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
8
2
Order By: Relevance
“…A modest antibody response has been previously detected in serum of Atlantic salmon affected by AGD (Akhlaghi et al. 1996; Gross et al. 2004b); however, in contrast with these studies, antibodies identified here are specific to wild‐type amoebae and are possibly directed against epitopes that are associated with virulence of Neoparamoeba sp.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…A modest antibody response has been previously detected in serum of Atlantic salmon affected by AGD (Akhlaghi et al. 1996; Gross et al. 2004b); however, in contrast with these studies, antibodies identified here are specific to wild‐type amoebae and are possibly directed against epitopes that are associated with virulence of Neoparamoeba sp.…”
Section: Discussioncontrasting
confidence: 95%
“…The subsequent processing of entrapped antigen may be facilitated by MHC‐II + cells that are present in gill lesions of Neoparamoeba sp.‐infected Atlantic salmon (Morrison, Koppang, Hordvik & Nowak 2006) resulting in the production of specific antibody. While detectable, yet modest systemic antibody has been previously reported in Atlantic salmon after contracting AGD (Akhlaghi, Munday, Rough & Whittington 1996; Gross, Carson & Nowak 2004b), these antibodies were detected after binding to cultured amoebae antigens. Neoparamoeba sp.…”
Section: Introductionmentioning
confidence: 76%
“…Previous investigations have reported the detection of serum anti-Neoparamoeba sp. antibodies in farmed Atlantic salmon [5]. However, Atlantic salmon infected with Neoparamoeba sp.…”
Section: Introductionmentioning
confidence: 98%
“…do not necessarily develop serum anti-Neoparamoeba sp. antibodies [5], and previously infected fish are not protected from reinfection upon subsequent re-exposure to Neoparamoeba sp. [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first described outbreaks of amoebic gill disease (AGD) in salmonids (Kent, Sawyer & Hedrick 1988; Roubal, Lester & Foster 1989; Munday, Foster, Roubal & Lester 1990; Munday, Lange, Foster, Lester & Handlinger 1993), a voluminous literature has been accumulated on various aspects of this disease. Many studies have focused on the Atlantic salmon, Salmo salar L., dealing with pathology (Nowak & Munday 1994; Rodger & McArdle 1996; Zilberg & Munday 2000; Adams & Nowak 2001, 2003, 2004a,b; Adams, Ellard & Nowak 2004), epidemiology (Clark & Nowak 1999; Douglas‐Helders, Nowak, Zilberg & Carson 2000; Douglas‐Helders, Saksida, Raverty & Nowak 2001a; Douglas‐Helders, Dawson, Carson & Nowak 2002; Douglas‐Helders, Handlinger, Carson & Nowak 2003a; Douglas‐Helders, O'Brien, McCorkell, Zilberg, Gross, Carson & Nowak 2003b; Douglas‐Helders, Tan, Carson & Nowak 2003c), immunology (Findlay, Helders, Munday & Gurney 1995; Akhlaghi, Munday, Rough & Whittington 1996; Findlay & Munday 1998, 2000; Findlay, Zilberg & Munday 2000; Zilberg & Munday 2001; Bridle, Butler & Nowak 2003; Gross, Carson & Nowak 2004a; Gross, Morrison, Butler & Nowak 2004b), diagnostic procedures (Zilberg, Nowak, Carson & Wagner 1999; Douglas‐Helders, Carson, Howard & Nowak 2001b) and treatment of AGD (Zilberg, Findlay, Girling & Munday 2000; Parsons, Nowak, Fisk & Powell 2001; Clark, Powell & Nowak 2003; Munday & Zilberg 2003; Roberts & Powell 2003). However, our present knowledge of AGD has been derived also from infections of other fish hosts (Dyková, Figueras & Novoa 1995; Dyková, Figueras, Novoa & Casal 1998; Dyková & Novoa 2001).…”
Section: Introductionmentioning
confidence: 99%